1991
DOI: 10.3312/jyio1952.23.6
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tracking of the migration routes of Whistling Swans Cygnus columbianus.

Abstract: or neck (one individual) of the swans. A total of 116 location data were obtained. The four swans went north along Sakhalin, and stayed around the mouth of Amur River or in northern Sakhalin for several days to nearly a month. In three of the four swans, the battery exhausted around the mouth of the Amur River or in northern Sakhalin, but one swan was successfully tracked to the breeding ground in tundra. The life of the batteries was expected to be two months but was in fact 30-46 days. The shorter duration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…In our study, seven tundra swan migration routes were identified for the EP flyway. One flyway directly crossing the Sea of Japan from Lake Nakaumi found by Kamiya and Ozaki (2002) was not detected in our study; however, all other flyways found by Higuchi et al (1991) and Kamiya and Ozaki (2002) were confirmed. The routes identified by Higuchi et al (1991) are considered to be equivalent to Routes A, B and likely Route E as well.…”
Section: Migration and Ep Flyway Of Tundra Swanssupporting
confidence: 32%
See 4 more Smart Citations
“…In our study, seven tundra swan migration routes were identified for the EP flyway. One flyway directly crossing the Sea of Japan from Lake Nakaumi found by Kamiya and Ozaki (2002) was not detected in our study; however, all other flyways found by Higuchi et al (1991) and Kamiya and Ozaki (2002) were confirmed. The routes identified by Higuchi et al (1991) are considered to be equivalent to Routes A, B and likely Route E as well.…”
Section: Migration and Ep Flyway Of Tundra Swanssupporting
confidence: 32%
“…One flyway directly crossing the Sea of Japan from Lake Nakaumi found by Kamiya and Ozaki (2002) was not detected in our study; however, all other flyways found by Higuchi et al (1991) and Kamiya and Ozaki (2002) were confirmed. The routes identified by Higuchi et al (1991) are considered to be equivalent to Routes A, B and likely Route E as well. Hence, there are at least 8 flyways in the EP flyway for Tundra Swans wintering in Japan: Seven routes (Routes A-G in Table 2) detected in this study, and one more flyway which directly crosses the Sea of Japan reported by Kamiya and Ozaki (2002) in previous study.…”
Section: Migration and Ep Flyway Of Tundra Swanssupporting
confidence: 32%
See 3 more Smart Citations